Analysis of Empathy Aspect Achievement in Reflective Narrative History Learning for Achieving 21st Century Competencies - Heri Susanto; Nurul Hidayati Utami; Meydisa Utami Tanau (Journal of Educational Sciences, 2026)
Empathy is vital for overcoming global challenges, such as humanitarian emergencies, political conflicts, violence, and other behavioral issues. Behaviors that reflect a lack of empathy include bullying, corruption, intolerance, radicalism, and violence—actions rooted in failing to consider others' perspectives. Between 2011 and 2019, the Indonesian Child Protection Commission (KPAI) received at least 37,381 bullying reports. Empathy indicates achievement of 21st-century competencies, namely critical reasoning, creativity, communication, and collaboration. Low empathy undermines efforts to build communication and collaboration skills. This study develops reflective narrative history learning to enhance empathy and 21st-century skills. Using the Research & Development (R&D) method and the 4-D instructional development model (Define, Design, Develop, Disseminate), 21 history teachers and 1,000 high school students in Banjarmasin City participated. Data were collected through interviews, a learning preferences questionnaire, and the Interpersonal Reactivity Index (IRI) to gauge students' empathy levels. Qualitative data were analyzed interactively, and quantitative data were analyzed with statistical tests. Results show that reflective narrative history learning effectively develops students' empathic concern.